OFR-65(2)-83 Reduction Of Land Recontouring Cost - Volume II - Bituminous Coal Field Northeast Arizona - J. W. Howland (The National Institute for Occupational Safety and Health (NIOSH), 1982)
A demonstration of dozer blades, designed for recontouring area-mined spoil and shown effective at Kansas and East Texas surface mine sites, was conducted at a Northeast Arizona surface coal mine to determine their effectiveness in different climate and soil conditions. The specialized tools were: 48-ft angle blade (on side-by-side tractor), 24-ft grading bar, modified 24-ft "U" blade (on side-by-side tractor), and a 13-ft deep "U" blade. Interest in the increased dirt-handling capacity of a previously built 22-ft blade, resulted in the design of a new Centerflow Blade of good versatility, able to maintain increased flow in otherwise difficult-to-move spoil. The demonstration involved 263 acres and showed a reduction of 50% in reclamation costs and 20% in fuel requirements for this mine site over conventional equipment. This savings resulted from improved technology, trained operators, and rigorous application of supervisory and monitoring techniques. Procedures and results of the demonstration are presented and analyzed here, along with guidelines for application of findings.